2008
DOI: 10.3189/002214308785837011
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of surface flow stripes and stratigraphic folds within Kamb Ice Stream: why don’t they match?

Abstract: ABSTRACT. Flow stripes seen in satellite imagery of ice streams and ice shelves are caused by surface undulations with kilometer-scale spacing and meter-scale relief and generally indicate current or recent fast ice flow. On a similar scale, folding of internal ice stratigraphy depicted in cross-flow icepenetrating radar profiles is also a common occurrence in ice streams, suggesting a possible relationship between the two sets of features. We have traced surface flow stripes in RADARSAT and MODIS imagery on K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Therefore, we cannot contribute qualitatively to the discussion of Campbell et al (2008), who have found no correlation between surface flow stripes of Kamb Ice Stream and signatures in radargrams crossing the ice stream.…”
Section: Synthesis Of the Datamentioning
confidence: 92%
“…Therefore, we cannot contribute qualitatively to the discussion of Campbell et al (2008), who have found no correlation between surface flow stripes of Kamb Ice Stream and signatures in radargrams crossing the ice stream.…”
Section: Synthesis Of the Datamentioning
confidence: 92%
“…Small-scale folding of kink style is observed in the highly anisotropic ice of the GISP2 ice core in Greenland (Alley et al, 1997b), consistent with Fletcher's theoretical results, although it appears that the longitudinal strain rate in this case may be extensional rather than compressional. Thorsteinsson and Waddington (2002) (Gudmundsson et al, 1998;Siegert et al, 2004;Campbell et al, 2008). Unlike sheath folds, which rotate to become parallel to the flow direction, these folds initiate in the flow direction, affect much of the ice column and are effectively transmitted by advection to the surface, where they are called flow stripes (Gudmundsson et al, 1998;Campbell et al, 2008).…”
Section: Foldsmentioning
confidence: 99%
“…4). After mapping and describing the pattern of surface features on the Antarctic Ice Sheet, we discuss their possible origin in relation to these three hypotheses and consider their relationship with internal ice-sheet features, such as buckled layers and folds inferred from radar studies (Conway et al, 2002;Campbell et al, 2008;Ross et al, 2011;Martín et al, 2014).…”
Section: Introductionmentioning
confidence: 99%